PET imaging of microglial pathology in multiple sclerosis - Hartiala, Olli; Tuomaala, Joel; Airas, Laura (Lippincott, 2026)
Purpose of review:
This review evaluates recent advances in the development of translocator protein (TSPO) – and purinergic receptor–binding PET tracers and highlights the capacity of TSPO-PET-imaging to capture microglial activation across multiple regions of interest in multiple sclerosis brain. We discuss the added value of integrating PET-derived measures with fluid and metabolic biomarkers, as well as their successful application in recent clinical trials.
Recent findings:
Recent research highlights PET as a robust molecular imaging tool for detecting microglial activation and implicates dysregulated microglial activity as a key driver of smouldering multiple sclerosis pathology. PET-detectable microglial activation appears not merely as a secondary response to neuroaxonal injury but is increasingly recognized as an integral inflammatory component of ongoing pathological processes that lead to future brain atrophy and clinical deterioration.
Summary:
Recent advances establish PET as an essential research tool for evaluating the presence of smouldering inflammation in MS brain not detectable using MRI. Furthermore, PET-based methods have proven suitable for measuring glial responses to potentially neuroprotective therapies currently under development.